Central Venous Pressure (CVP) Reduction Associated With Higher Cardiac Output (CO) Favors Good Prognosis of Circulatory Shock: A Single-Center, Retrospective Cohort Study - Su, Longxiang; Pan, Pan; Li, Dongkai; Zhang, Qing; Zhou, Xiang; Long, Yun; Wang, Xiaoting; Liu, Dawei (Frontiers in Medicine, 2019)
Backgrounds. Frank-Starling curve is the basis of hemodynamics. Changes in cardiac output (CO) caused by central venous pressure (CVP) are the most important concerns in the treatment of critically ill patients. Objectives. How to use CVP and what its relevant mechanisms with respect to CO should be explored in clinic. Methods. A total of 134 patients with circulatory shock were retrospectively included and analyzed. Hemodynamic data were recorded and analyzed at PICCO initiation and 24 hr after PICCO. Data regarding 28-day mortality and renal function were also collected. Results. The patients were divided into a CVP↑+ CO↑ group (n=23), a CVP↑+ CO↓ group (n=29), a CVP↓+ CO↑ group (n=44), and a CVP↓+ CO↓ group (n=38) based on PICCO initiation and 24 hr after PICCO. Post hoc tests showed the CVP↓+ CO↑ group had higher 28-day survival than the other groups [log rank (Mantel-Cox)=8.758, P=0.033]. In terms of hemodynamic characteristics, the CVP↓+ CO↑ group had a lower cardiac function index (CFI) (4.1±1.4 /min) and higher extravascular lung water index (EVLWI) (11.0±4.7 ml/kg) at PICCO initiation. This group used more cardiotonic drugs (77.3%, P<0.001) and had a negative fluid balance (-780.4±1720.6 ml/24 hr, P=0.018) 24 hr after PICCO than the other three groups. Cardiotonic drug use and dehydration treatment was associated with increased CFI (from 4.1±1.4 /min to 4.5±1.3/min, P=0.07) and reduced ELVWI (from 11.0±4.7 ml/kg to 9.0±3.5 ml/kg, P=0.029). Renal function tests showed that SCr and BUN levels in the CVP↓+ CO↑ group were significantly improved (SCr from 197.1±128.9 mmol/L to 154.4±90.8 mmol/L；BUN from 14.3 umol/L±7.3 to 11.6±7.0 umol/L, P<0.05). Conclusions. Lower CVP associated with CO increased, which may improve 28-day prognosis in patients with circulatory shock. Higher CO derived from lower CVP may also contribute to renal function improvement.